“I Know Much Better than You Do”. British Ambassadors to Austria in Conflict with their Government, 1848–1855 - Lukas Fallwickl (Österreichische Zeitschrift für Geschichtswissenschaften)
In much the same way as today, nineteenth-century diplomats were expected to represent their government politically abroad and implement foreign policy as decided by their superiors. However, quite a few of them held personal views that conflicted with their instructions, causing numerous difficulties. British diplomats sent to the Habsburg Monarchy provide a prime example of this problem, with Anglo-Austrian relations strained by ideological conflicts and British ambassadors repeatedly ending up supporting the Austrian point of view. This article uses two of them, Lord Ponsonby and Lord Westmorland, as case studies, focusing on their diplomatic practice and the changing relationships with their superiors. It examines the extent of their agency, the consequences of rebellious behaviour, and their ability to influence British foreign policy according to their own convictions.